MELIHAT KEMBALI KONSEP MASHLAHAH DALAM KASUS PENEMBAKAN LASKAR FRONT PEMBELA ISLAM - Ahmad Muhtadi Anshor (Fakultas Agama Islam Universitas Wiralodra, 2022)
This study aims to revisit the priority aspects of the state's interests and protection of the soul from the mashlahah perspective. This is so urgent when recently shocked by the shooting of a member of the Islamic Defenders Front (FPI) laskar by a member of the Indonesian National Police. The result of this case was the emergence of various controversies from humanitarian activists, human rights, and moderate state defenders. This phenomenon is certainly something that needs to be resolved with a model approach in the Islamic legal discourse, namely the mashlahah concept. The concept of mashlahah is seen as a more adaptive concept in responding to various contemporary problems, including seeing the shooting case of a member of the Islamic Defenders Front (FPI) army. This literature-based study found that the shooting of members of the FPI paramilitary apparatus by the police was based on prioritizing the public interest of the state (mashlahah al-'ammah) rather than personal or group interests (mashlahah al-fardhiyyah). Meanwhile, the determination of mashlahah between the interests of the state (public) and private interests (groups) is based on taking less mafsadat.